3PC-004 What happens when insulin aspart is diluted in dextrose?. (March 2019) - Préta, LH; Henry, H; Masse, M; Carta, N; Kouach, M; Foulon, C; Goossens, JF; Lannoy, D; Genay, S; Decaudin, B; Odou, P
Abstract : Background: In hospital, medications for infusion are mostly diluted in saline. In neonatal resuscitation, glycaemic instabilities are frequently observed in premature newborns, hence insulin treatment is started. In our establishment, insulin aspart is used and diluted in a 5% dextrose solution (D5%), due to sodium restrictions in newborns. Purpose: To evaluate the impact of the choice of D5% diluent on the stability of the insulin aspart at 1 U/mL. Material and methods: The pharmaceutical specialty composed of insulin aspart and its two preservatives (phenol and metacresol) were diluted in saline or D5%. The impact of the diluent on the stability of insulin aspart was studied by high-performance liquid chromatography with UV detection (HPLC-UV). A stability indicator method, 1 adapted from the method of Poulsen et al . 2 and developed for insulin aspart diluted in saline, was used. The prospective formation of a new compound in the different diluents was evaluated by HPLC with a mass spectrometry detection (HPLC-MS) in full-scan mode. The kinetic of the new compound's appearance was studied by relative evaluation of HPLC-UV signals during 1 week for insulin at 1 U/mL diluted in D5% (n=4). Results: The three products contained in the pharmaceutical specialty diluted in saline correspond to the three signals identified in HPLC-UV (elution order: phenol, metacresol and insulin aspart). After dilution of insulin aspart in D5%, we noted a fourth signal. pH influence and forced degradation tests failed to attribute this signal to insulin or preservatives' degradation. HPLC-MS analysis revealed a mass difference of 162 daltons between insulin and this product, which corresponds to a glycation phenomenon of insulin aspart. Finally, the kinetics shows that the insulin glycation phenomenon seems to increase with the contact time between insulin and glucose until a plateau is reached after 24 hour of contact. Conclusion: This work highlighted the instability of insulin in D5% and showed the phenomenon of insulin aspart glycation. To better characterise this phenomenon, the biological effect of glycation on insulin activity have to be determined, since a decrease in activity has been observed for human insulin. References and/or acknowledgements: 1. Methodological guidelines for stability studies of hospital pharmaceutical preparations . https://www.gerpac.eu/IMG/pdf/guide_stabilite_anglais.pdf 2. Poulsen, et al. Pharmal Res 2008. No conflict of interest.